2023
DOI: 10.3389/fped.2023.1123405
|View full text |Cite
|
Sign up to set email alerts
|

End organ perfusion and pediatric microcirculation assessment

Grace M. Arteaga,
Sheri Crow

Abstract: Cardiovascular instability and reduced oxygenation are regular perioperative critical events associated with anesthesia requiring intervention in neonates and young infants. This review article addresses the current modalities of assessing this population's adequate end-organ perfusion in the perioperative period. Assuring adequate tissue oxygenation in critically ill infants is based on parameters that measure acceptable macrocirculatory hemodynamic parameters such as vital signs (mean arterial blood pressure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Patients who had received fluid resuscitation within the 24 hours prior to PICU admission were not included either. Recently, our group found that unbalanced crystalloids could alter the microcirculation and we wanted to control for this confounding factor from the design ( 13 ). The septic shock definition proposed in the SSC and the Latin American Consensus was used ( 1 , 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients who had received fluid resuscitation within the 24 hours prior to PICU admission were not included either. Recently, our group found that unbalanced crystalloids could alter the microcirculation and we wanted to control for this confounding factor from the design ( 13 ). The septic shock definition proposed in the SSC and the Latin American Consensus was used ( 1 , 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…The currently available technology (like sublingual video microscopy) allows direct observation of microcirculation changes and indirect observation of endothelial glycocalyx degradation in the pediatric population ( 12 ). In children with septic shock, this microvascular technology has found less perfused capillary density and greater perfusion heterogeneity ( 13 ). Our hypothesis is that milrinone not only improves macro-hemodynamics, but its direct vasodilating effects can also be seen in the micro-hemodynamics of children with sepsis.…”
Section: Introductionmentioning
confidence: 99%
“…Very few studies have assessed both macro- and microcirculation in children with sepsis [65 ▪ ]. Paize et al found microcirculatory alterations despite a normal CO in children with meningococcal septic shock [25], and Top et al found persistent low microcirculatory vessel density in children who died from septic shock [2].…”
Section: Relationship Between Macro and Microcirculationmentioning
confidence: 99%